Study of Architectural Form and Structural Analysis of Central Tower Cluster of Angkor Wat - Vacharee Svamivastu; Komsan Maleesee (Sensors and Materials, 2025)
follows-formIn this study, we investigated the form and structure of the Angkor Wat temple complex using diagrams, ogive geometry, and structural analysis.The findings of previous research indicated the appropriate basic grid-cell size for the temple complex's planning.They were used as the main data for this research.An earlier analysis revealed the geometric code (basic module, BM) that controls the architectural design diagram and construction of the temple complex.The use of a center-shifting technique to avoid the numerical fractions occurring in grid cell modules resulted in the asymmetry of the temple, as evidenced by the unequal openings (windows) on the left and right sides of the first enclosure.The diagram 5:6, suitable for the inhabitants who were the Vaiyas, is achieved by the center-shifting technique.The form analysis showed that the towers in the temple were of ogive shape of varying sizes, corresponding to Pythagoras' common-right-triangle combinations.The structural analysis demonstrated the use of low-tiered walls around the core structure of the central tower cluster, increasing the wall bearing of the core structure with exceptionally large wall corners to strengthen the bearing walls of the core structure.As a result, the maximum weight-induced deformation of the central tower cluster indicates the capability of the walls to sustain massive weights.An Angkor Wat central tower cluster was constructed on a slant base foundation.In this research, we unveiled the structurefollows-form and form-follows-structure principles in the construction of the Angkor Wat temple.
Keywords: Masonry and Concrete Structural Analysis; Architecture and Cultural Influences; Architectural and Urban Studies